2013
DOI: 10.1159/000348756
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 Inhibitors as Therapeutic Modulators of Immune Cell Function and Associated Cardiovascular and Renal Insulin Resistance in Obesity and Diabetes

Abstract: The prevalence of obesity and diabetes continues to rise in the United States and worldwide. These findings parallel the expansion of childhood obesity and diabetes. Obesity is a central component of the cardiorenal metabolic syndrome (CRS) which increases the risk for cardiovascular disease (CVD) and chronic kidney disease (CKD). The hallmark of obesity, CRS, and early type 2 diabetes is insulin resistance, a result of decreased insulin metabolic signaling due, in part, to enhanced serine phosphorylation and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 153 publications
0
54
0
Order By: Relevance
“…Interestingly, a decrease in inflammatory macrophage accumulation has been observed in adipose tissue and atherosclerotic lesions following treatment with DPP-4 inhibitors [38,39]. It is thus possible to suggest that sitagliptin might exert an anti-inflammatory effect on EAT as recently found with other anti-inflammatory drugs [40,41].…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, a decrease in inflammatory macrophage accumulation has been observed in adipose tissue and atherosclerotic lesions following treatment with DPP-4 inhibitors [38,39]. It is thus possible to suggest that sitagliptin might exert an anti-inflammatory effect on EAT as recently found with other anti-inflammatory drugs [40,41].…”
Section: Discussionmentioning
confidence: 76%
“…The hindgut hypothesis states that food will stimulate L cells in the ileum to secrete GLP-1, which can improve glucose homeostasis [7]. The role of GLP-1 in improving insulin sensitivity has been confirmed [28], and GLP-1 analogs have been proposed for patients with type 2 diabetes [29]. Previous studies have also shown that SG and RYGB procedures increase GLP-1 secretion [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also expressed in other immune cells and nonimmune cells/tissues (5,202). Tissues/ organs expressing DPP-4 include blood vessels, adipose tissue, kidney, liver, pancreas, lymph nodes, spleen, bone, brain, lung, prostate, thymus, and uterus (109,202).…”
Section: Dpp-4 Biology and Pharmacologymentioning
confidence: 99%
“…Vascular dysfunction is the critical factor in progression to CVD and CKD and the associated vasculopathies that constitute early derangements mediating progression to end organ damage (5,8,137,138). Vascular dysfunction is independently associated with CVD complications, including stroke, atherosclerosis, and heart and kidney disease (8,135).…”
Section: Cellular and Molecular Mechanisms Of Action Of Dpp-4i In Thementioning
confidence: 99%
See 1 more Smart Citation